Comparative study of physiochemical properties of available commercial grade Mustard oil of Bangladesh - Sultana, Razia; Shill, Somnath; Bachar, Sitesh Chandra (Journal of Biomedical and Pharmaceutical Research, 2018)
Mustard oil, commonly used vegetable oil in Bangladesh containing low saturated fat compared to other cooking oils and enriched with essential vitamins. The purpose of the present study was to evaluate the quality of commercially available mustard oil samples and also to inspect the physicochemical properties according to standard procedures. Therefore, nine commercial grade samples of Bangladesh were collected and subjected to physiochemical tests like density, pH, moisture content, saponification value, iodine value, acid value, ester Value, and peroxide value etc. according to the the standard procedures of AOAC directed titrimetric method.The obtained results were compared with the standard values of BSTI .Statistical analysis like Mean ± SD and one sample t-test were performed on all the obtained data. The pH value (4.73±0.14) of all samples was within acidic region, moisture content value was0.19±0.05 density was0.78±0.03. The saponification value of all samples was177.36±2.88 ,the Iodine value was 106.78±1.84 and Ester value was 176.2±2.89 that was quite normal within the range .In terms of acid value (1.12±0.04), all samples were outside the specified range( P value was significantly different P<0.05) . The peroxide value (10.03±0.18) of some mustard oil samples were found to comply with the specification (P value was not significantly different P<0.05) and five of them have relatively higher range. The consumers using this specious product must be careful because it may be harmful even physicochemical parameters are outside of the specifications. Keywords:Saponification value; iodine & peroxide value; acid &ester Value; density; pH; moisture content.